Critical Success Factors (CSF) for ERP : Hospital University Science Malaysia (HUSM) / Azwani Awang - Awang, Azwani (2006)
This research project involves an investigation and identification of critical success factors (CSF) in the ERP system exists in Hospital University Science Malaysia (HUSM). The environment of HUSM is divided into two, which are the hospital environment and the university environment. This research is mostly focusing on the university environment. This research is done based on an extensive literature review done recently. From the extensive literature review, 20 unique CSF in the model were identified. However none of these factors focused specifically on the system in HUSM. The ERP model developed is divided into 4 factors for consideration, which are strategic factors, the organizational context, tactical factors, and technological context. It was found that interviewed discussed 16 of the 29 factors identified from literature, and also addressing 4 new factors that were not identified earlier in the literature. These new factors concerned competitive edge, service for students, knowledge management and system ownership. It was also found that although 5 of the factors were addressed, some of the factors were addressed more frequently than others during the interviews. This research gave an important insight into the implementation school of IS while adding theory and knowledge with a focus on ERP implementation within a university environment (livari 1991). Therefore it is hoped that future ERP implementations can draw upon and learn from this research project. The author calls for a further investigation into the relationships between the different factors found to contribute to the possibility of a successful ERP implementation in a university environment and a future comparison between different ERP implementations in other university sites and the differences in the CSF's that might exist.